From mining to markets: The evolution of bitcoin transaction fees - Easley, David; O'Hara, Maureen; Basu, Soumya (Journal of Financial Economics, 2019)
We investigate the role that transaction fees play in the bitcoin blockchain's evolution from a mining-based structure to a market-based ecology. We develop a game-theoretic model to explain the factors leading to the emergence of transactions fees, as well as to explain the strategic behavior of miners and users. Our model highlights the role played by mining rewards, transaction fees, price, and waiting time, discusses welfare issues, and examines how microstructure features such as exogenous structural constraints influence the dynamics of user participation on the blockchain. We provide empirical evidence on the model's predictions and discuss implications for bitcoin's evolution.